The The Analysis of Lead (Pb) Contents in Tuna (Thunnus sp.) Using Furnace Graph of Atomic Absorption Spectrophotometry Method: Keywords: CRM Standard; Lead (Pb); AAS; Tuna (Thunnus sp.) - eriyusni Tanjung (AQUACOASTMARINE: Journal of Aquatic and Fisheries Sciences, 2023)
Abstract: This research aimed to determine of Pb value in tuna (Thunnus sp) and accordance with WHO (World Health Organization), European Union as standard limits and to determine of tuna Pb value in the CRM (Certified Reference Materials). The 5 tuna fish sampling was conducting in some of Medan traditional markets such as; Belawan, Pancing, Petisah, Padang Bulan, and Sei Kambing. The Lead of (Pb) in Tuna (Thunnus sp) was determines by using Furnace graph of AAS (Atomic Absorption Spectrophotometry) method. The laboratory result indicated that the highest Pb value was found in Belawan Market sample with the value of 0.070 ml/kg and lowest was found in the sample from Petisah Market was found the value of 0.010 ml/kg. And the Pb value in Certified Reference Materials (CRM) was still in the CRM with value of 0.404 Â± 0.062 ml/kg.